Comparison of vascular access patency and patient survival between native arteriovenous fistula and synthetic arteriovenous graft according to age group. Issue 3 (5th May 2020) - Choi, Joonsung; Ban, Tae Hyun; Choi, Bum Soon; Baik, Jun Hyun; Kim, Byung Soo; Kim, Young Ok; Park, Cheol Whee; Yang, Chul Woo; Jin, Dong Chan; Park, Hoon Suk
Abstract: Introduction: Arteriovenous fistula (AVF) is historically known to be the ideal option for vascular access (VA) for hemodialysis compared with arteriovenous graft (AVG). However, this approach has been recently questioned in the aging population because of their poor vessel quality and multiple comorbidities. Methods: Data from a total of 2200 patients from the VA category of The Catholic Medical Center nephrology registry from March 2009 to February 2017 were analyzed. We compared VA patency and patient survival between two groups, AVF and AVG, according to age. Findings: Compared with the AVG group, survival benefit in the AVF group continued even in patients ≥80 years. In the whole population, all the primary patency (PP), primary‐assisted patency (PAP), and secondary patency (SP) measures were superior in the AVF group. With regard to subgroups, PP was comparable between the two groups in patients ≥65 years, whereas PAP and SP were superior in the AVF group even in septuagenarian patients who are from 70 to 79 years old. In patients ≥80 years, all the patency measures were comparable between the two groups. When the separate comparison of lower‐arm AVF (or upper‐arm AVF) and AVG, lower‐arm AVF failed to demonstrate its superiority in any kind of patency in septuagenarian patients compared with AVG, whereas upper‐arm AVF demonstrated its superiority in PAP and SP in septuagenarian patients. However, even upper‐arm AVF failed to demonstrate its superiority in any kind of patency in patients ≥80 years. Discussion: Arteriovenous fistula if using upper‐arm vessel showed the superior VA patency up to septuagenarian patients, whereas, in HD patients ≥80 years, AVF and AVG were comparable in VA patency.